Optimization of placenta extraction for wound healing activity - Warintorn Ruksiriwanich (2020)
© 2019, Chiang Mai University. All rights reserved. This study aimed to optimize the extraction method for placenta which gave the highest biological content and activity using a central composite face-centered experimental design model. The effects of temperature and pH were selected to investigate for 2 responses, the ABTS scavenging activity and total protein on placenta extraction. Then, the optimized method was implemented to compare the wound healing effects on fibroblast cell migration and endothelial cell tube formation between porcine and Aries placenta extracts. The optimal extraction method which gave the highest trolox equivalent and total protein content was pH 9.07 and at 50°C. This optimal extraction condition gave the non-significant biological contents and activities of porcine and Aries placenta extracts. The Aries placenta extract gave higher total protein content and ABTS scavenging activity, but lower elastase and collagenase inhibition activity than those of porcine extract. Both Aries and porcine placenta extracts gave higher percentages of wound closure, cell migration rate and significantly longer in the capillary length than those of the standard L-ascorbic acid. Both placenta extracts from the optimized method showed potential effects on wound healing on fibroblast cell migration and endothelial cell tube formation which can be studied for the further wound healing investigation.